Tradisi Penyembuhan Orang Sakit Melalui Upacara Belian dan Perbandingannya dengan Sakramen Pengurapan Orang Sakit - Sandy Julianus; G. Simon Devung; Wilfridus Samdirgawijaya (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2021)
The research aims to find out the similarities and differences between Belian and the Sacrament Anointing of The Sick. The similarities and differences can be seen through the concept of disease and the concept of healing. The research was conducted at Tanjung Isuy and Tanjung Jan Villages. The research method used was descriptive qualitative and data collection techniques used were interviews, observation, and documentation study. The number of informants in the study was six people. Based on the research result, the researcher finds similarities and differences in the concept of disease and the concept of healing. Similarities and differences can be seen through several elements, namely: the reason why humans are sick, the types and forms of the disease, the subject causing illness, and the process of being sick. Then the similarities and differences in the concept of healing can be seen in the way of healing, the cause of healing, the subject who has the power to heal, the reason for the disease to heal, and the human process of being healed.